2018
DOI: 10.3390/ijerph15112592
|View full text |Cite
|
Sign up to set email alerts
|

Long Working Hours and Job Quality in Europe: Gender and Welfare State Differences

Abstract: Chronic extreme long working hours (LWH) have been found consistently associated with poor health status. However, the evidence for moderately LWH (41–60 h a week) is contradictory. Although poor job quality has been proposed as one of the mechanisms of this relationship, there are almost no studies about LWH and job quality. The objectives of this study were to analyze the association between moderately LWH and job quality in the EU27, as well as to examine differences by welfare regimes and gender. This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…• Average number of usual weekly hours of work in the main job (WH). The WB has been explored in studies that intend to investigate the impact of long working hours on job quality (Artazcoz et al, 2018). The average number of working hours in the EU has remained relatively steady despite a trend over the last 10 years of a small reduction (average for 2009 was 38.3 hours and for 2018 is 37.9 hours).…”
Section: Datamentioning
confidence: 99%
“…• Average number of usual weekly hours of work in the main job (WH). The WB has been explored in studies that intend to investigate the impact of long working hours on job quality (Artazcoz et al, 2018). The average number of working hours in the EU has remained relatively steady despite a trend over the last 10 years of a small reduction (average for 2009 was 38.3 hours and for 2018 is 37.9 hours).…”
Section: Datamentioning
confidence: 99%
“…Also, the effect on sleep and mental health when workers work long hours (Afonso et al, 2017); the effects of extended hours on the health of shift workers (Harrington, 2001). But according to Artazcoz et al (2018), the conclusions of these and other studies have been mainly contradictory. These studies define long working hours as working in excess of between 40 to 55 hours per week, and in some extreme cases in Asia where they work for upwards 60 hours per week with a commonly practiced system referred to as 996 (from 9:00 am to 9:00 pm, 6 times a week) (Virtanen & Kivimaki, 2018).…”
Section: Literature and Theoretical Reviewmentioning
confidence: 99%
“…Also, Van Der Hulst & Geurts (2001) concluded that in low motivated situations, involuntary overtime might lead to mental health issues, which may then suggest that when long working hours occur in poor quality jobs. However, it is considered a significant risk because of the health impact as compared to spending long work hours in professional and more rewarding careers (Beckers et al, 2004;Johnson & Lipscomb, 2006;Artazcoz et al, 2018).…”
Section: Literature and Theoretical Reviewmentioning
confidence: 99%
“…Also, a report conducted by the Organization for Economic Cooperation and Development (OECD) in 2019 indicated that time spent in paid work reduced below 40 h in most countries in Europe, with Netherland, Norway, and Switzerland reporting the lowest working hours respectively ( 3 ). Despite these reductions, there are several reports about longer hours in paid work in many countries including United Kingdom, Eastern European countries ( 4 ), Israel, Costa Rica, Mexico, Columbia, Turkey ( 5 ), China, Korea, Japan ( 2 ). This may be due to increased workload, tight deadlines, organizational commitment, recognition, promotion, and job insecurity that many workers experience ( 6 ).…”
Section: Introductionmentioning
confidence: 99%